Agua, conflicto y cambio climático en los Andes - Guevara Gil, Armando (2023)
It is surprising that the theme of water and hydrographic basins does not occupy a central place in research and training in Social Sciences, Humanities and Law in Peru. There are important interdisciplinary academic initiatives, by the way. But any review of the bibliographic production and the curricula of the ninety-five licensed universities in our country will show, by flagrant omission, that water and basins do not arouse the interest or concern of our university community. Naturally, we have a host of brilliant researchers, Peruvians and Peruvians, who have been dedicated to the interdisciplinary study of water for decades. But they are a minority, and despite their efforts, water has not become a thematic axis of the national academic or political agenda.